2007
DOI: 10.1242/jcs.002527
|View full text |Cite
|
Sign up to set email alerts
|

Traction force microscopy in Dictyostelium reveals distinct roles for myosin II motor and actin-crosslinking activity in polarized cell movement

Abstract: Continuous cell movement requires the coordination of protrusive forces at the leading edge with contractile forces at the rear of the cell. Myosin II is required to generate the necessary contractile force to facilitate retraction; however, Dictyostelium cells that lack myosin II (mhcA–) are still motile. To directly investigate the role of myosin II in contractility we used a gelatin traction force assay to measure the magnitude and dynamic redistribution of traction stresses generated by randomly moving wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
85
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 46 publications
10
85
2
Order By: Relevance
“…They claimed that myosin II motor and actin crosslinking activity were both required to develop and maintain asymmetrical patterns of traction stress, but they found that asymmetrical distributions sometimes even developed in myosin-II-null cells. These findings have led us to raise two questions: first, are there rearward traction stresses at the front of cells, as suggested by Uchida et al (Uchida et al, 2003), Tsujioka et al (Tsujioka et al, 2004), Ladam et al (Ladam et al, 2005) and del Alamo et al (del Alamo et al, 2007), or not, as suggested by Lombardi et al (Lombardi et al, 2007)? Second, if not, then what is the source of myosin-II-independent traction stress at the rear of myosin-II-null cells?…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…They claimed that myosin II motor and actin crosslinking activity were both required to develop and maintain asymmetrical patterns of traction stress, but they found that asymmetrical distributions sometimes even developed in myosin-II-null cells. These findings have led us to raise two questions: first, are there rearward traction stresses at the front of cells, as suggested by Uchida et al (Uchida et al, 2003), Tsujioka et al (Tsujioka et al, 2004), Ladam et al (Ladam et al, 2005) and del Alamo et al (del Alamo et al, 2007), or not, as suggested by Lombardi et al (Lombardi et al, 2007)? Second, if not, then what is the source of myosin-II-independent traction stress at the rear of myosin-II-null cells?…”
Section: Introductionmentioning
confidence: 95%
“…Tsujioka and colleagues (Tsujioka et al, 2004) also detected rearward traction stresses in migrating Dictyostelium cells. Recently, Lombardi et al (Lombardi et al, 2007) mapped traction stresses in migrating vegetative Dictyostelium cells. They found a lack of traction stress at the front but high stress at the rear of the cells, in contrast to Uchida et al (Uchida et al, 2003), It has been suggested that myosin II exerts traction forces at the posterior ends and retracting pseudopodia of migrating cells, but there is no direct evidence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum force of large fibroblasts is several tens of kilopascals (Dembo and Wang, 1999;Munevar et al, 2001aMunevar et al, , 2001b, although that of small cell types, such as Dictyostelium cells (Iwadate and Yumura, 2008a;Lombardi et al, 2007;Tanimoto and Sano, 2014), is several kilopascals or smaller. The magnitude of the traction forces may be related to cell size.…”
Section: Introductionmentioning
confidence: 99%
“…Use of a recently developed digital volume correlation (DVC) method (16) allows 3-D displacements and traction fields to be determined directly from volumetric confocal image stacks, and obviates the need for complex inverse formulations (10). The method has a temporal resolution that permits confocal imaging over time scales relevant for the migration of anchorage dependent cells, such as endothelial cells and fibroblasts (17).…”
mentioning
confidence: 99%